A Nodular Pink Lesion with an Uncommon Diagnosis: A Quiz - Maria Beatrice del Giudice; Marco Brusasco; Miriam Rovesti; Roberta Manuguerra; Michele Maria Dominici; Alfredo Zucchi; Claudio Feliciani; Ignazio Stanganelli (Medical Journals Sweden, 2020)
Abstract is missing (Quiz)